Liberdade e tolerância em Nicolau de Cusa: a idéia de sistema através da análise de conceitos - Jose Ricardo Sousa Rodrigues (2006)
We argue, against the view held by Ernest Cassirer, that the notion of a systematic thought cannot be applied to the integrity of Nicholas of Cusas philosophy. We begin by identifying a division in Cusas thought in two thematic groups (a philosophy of adequation and a philosophy of composition) and analyzing the presence of these two concepts in his works we conclude that Cassirers view is inadequate, above all in what concerns the specific topics of the practical philosophy. The main upshot is the recognition that Cusa belongs to the plural and formally free environment of the Renaissance, in which a variety of fractionated concepts, themes, types of writings and concerns are admitted.